USE OF THE HIGH-FLOW HELMET CPAP NON-INVASIVE VENTILATION DEVICE DESIGNED IN PERU IN PATIENTS WITH SEVERE ACUTE RESPIRATORY SYNDROME (COVID-19): A PROSPECTIVE MULTICENTER STUDY - MANTARI, JOSÉ LUIS (2024)
HIGH-FLOW NON-INVASIVE VENTILATION (NIV) DEVICES REDUCE THE MORBIDITY AND MORTALITY OF COVID-19. THE OBJECTIVE WAS TO EVALUATE THE USE OF THE NON-INVASIVE VENTILATION DEVICE WITH HIGH-FLOW HELMET CPAP DESIGNED IN PERU IN PATIENTS WITH SEVERE ACUTE RESPIRATORY SYNDROME (COVID-19) HOSPITALIZED IN THE EMERGENCY SERVICES OF FIVE HOSPITALS. PROSPECTIVE MULTICENTER AND CROSS-SECTIONAL OBSERVATIONAL STUDY FROM FIVE HOSPITALS FROM JULY TO AUGUST 2020. 19 PATIENTS WERE RECRUITED AND DIVIDED INTO TWO GROUPS (G-1 N = 10; G-2 N = 9) APPLYING CLINICAL AND GASOMETRIC PARAMETERS AS INDICATORS OF DISEASE EVOLUTION UPON HOSPITAL ADMISSION AND WITHIN 24 HOURS. A PROGRESSIVE INCREASE IN THESE PARAMETERS WAS OBSERVED IN THOSE PATIENTS WHO USED THE NIV CPAP HELMET WITHIN THE FIRST 24 HOURS. IN G-01, IMPROVEMENT WAS EVIDENT IN 90% (N = 9/10): PAO2 (RANGE 48–137; AVERAGE: 82.49 ± 8.07; P-VALUE = 0.008), CO2 (25.2–51.0; 36.62 ± 2.62; P-VALUE P = 0.327), AND THE PAO2/FIO2 COEFFICIENT (87–318; 191.5 ± 18.68). 10% OF PATIENTS DID NOT PROGRESS OPTIMALLY, BEING SUBJECTED TO ENDOTRACHEAL INTUBATION AND INVASIVE MECHANICAL VENTILATION. IN G-02 THE VALUES WERE %SATO2 (RANGE 92–98; 96 ± 0.76) AND THE SAO2/FIO2 COEFFICIENT (214–228; 223.2 ± 1.80), INDICATING SIGNIFICANT IMPROVEMENT WITHIN 24 HOURS (P < 0.001). IT IS CONCLUDED THAT THE USE OF THE CPAP HELMET NON-INVASIVE VENTILATION (NIV) DEVICE CONTRIBUTES TO IMPROVING GASOMETRIC VALUES AND CLINICAL CONDITION. BEING AN ALTERNATIVE TO RECOVER TYPICAL CASES OF COVID-19 IN ALL HOSPITALS IN PERU. COPYRIGHT MANTARI JL ET AL. THIS IS AN OPEN ACCESS ARTICLE DISTRIBUTED UNDER THE TERMS OF THE CREATIVE COMMONS ATTRIBUTION LICENSE (CC-BY 4.0), WHICH PERMITS UNRESTRICTED USE, DISTRIBUTION, AND REPRODUCTION IN ANY MEDIUM, PROVIDED THE ORIGINAL AUTHOR AND SOURCE ARE CREDITED.